2020
DOI: 10.1016/j.aller.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with wheezing among Lebanese children: Results of a cross-sectional study

Abstract: Background: In Lebanon, asthma is underdiagnosed due to low access to healthcare, particularly in rural areas, although asthma diagnosis in children is based mainly on clinical symptoms. Thus, wheezing might be more suggestive of undiagnosed respiratory diseases including asthma in Lebanese children. This study aimed to determine the factors associated with wheezing in Lebanese children without asthma diagnosis. Methods: This cross-sectional study was conducted between December 2015 and April 2016, enrolling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…Previous studies can show more details about the questionnaire. [28][29][30][31][32][33][34][35][36] The questions that assessed OTC medications used during pregnancy encompassed the most studied medications that showed a correlation with an asthma diagnosis, that is, antibiotics, [11][12][13][14] paracetamol, 15 vitamin D, [20][21] anti-reflux and acid-suppressive drugs, [24][25][26] ibuprofen, 27 and vitamin C. 37 The frequencies of intake were divided into the following: never or occasionally, once every month, one-three times every month, once every week, two to four times a week, and more than five times a week. In some drugs variables, the frequencies were collapsed into several levels where cells do not contain 0.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous studies can show more details about the questionnaire. [28][29][30][31][32][33][34][35][36] The questions that assessed OTC medications used during pregnancy encompassed the most studied medications that showed a correlation with an asthma diagnosis, that is, antibiotics, [11][12][13][14] paracetamol, 15 vitamin D, [20][21] anti-reflux and acid-suppressive drugs, [24][25][26] ibuprofen, 27 and vitamin C. 37 The frequencies of intake were divided into the following: never or occasionally, once every month, one-three times every month, once every week, two to four times a week, and more than five times a week. In some drugs variables, the frequencies were collapsed into several levels where cells do not contain 0.…”
Section: Data Collectionmentioning
confidence: 99%
“…The same questionnaire had already been used in Lebanon in studies with older children. [32][33][34][35] The first part of the questionnaire assessed the socio-demographic characteristics of the children, including age, gender, region, number of rooms and number of persons living in the house, education level of both parents (assessed based on the number of years of schooling, i.e., illiterate, primary, complementary, secondary, university), family history of asthma, and other known risk factors of asthma (the heating system used at home, child history of recurrent otitis, humidity inside the house, child attending a nursery, etc. ).…”
Section: Hygiene Measures and Asthmamentioning
confidence: 99%
“…101,102 Mobility restrictions further increased children's time spent indoors, being more prone to indoor air pollution. Some studies in the EMR showed positive associations between children's (between 6 months and 15 years old) exposures to indoor stressors, such as Arabian incense burning, 103,104 second hand smoking, 105,106 indoor pollutants and allergens, [107][108][109][110][111][112] and house dust mite 110 and a suite of respiratory and neurologic health outcomes (such as asthma, respiratory complaints and lung function) in countries of the EMR region (Oman, Egypt, Qatar, Iran, Kuwait, Saudi Arabia, Sudan, Lebanon and Libya). Other forms of indoor pollution arising from poor housing and infrastructure conditions (such as mold, damp walls and floors, leaking pipes) were linked to adverse acute and chronic health effects among children.…”
Section: Understudied Exposome Components Of Children's Health In the Emrmentioning
confidence: 99%